A social network model driven by events and interests. Issue 9 (1st June 2015) - Sun, Xiaoling; Lin, Hongfei; Xu, Kan
Highlights An agent-based model for social network modeling is proposed. The model merges the attribute-based and structure-based dynamical processes. The evolution of the model is driven by events and interests. The model is capable of reproducing many realistic network statistics and patterns.